Cholera in Sub-Saharan Africa: Unveiling neglected drivers and pathways to elimination - (:unkn) unknown (My University, 2025)
Cholera is a virulent infectious disease caused by the Gram-negative, comma-shaped bacteria Vibrio cholerae, after ingesting contaminated food and/or water. If left untreated, it can kill within 5 days. Since mid-2021 the world has recorded a notable increase in the seventh cholera pandemic, with high case fatality rate especially in Sub-Saharan Africa. Oral cholera vaccines are established but not readily available on the market, or if they are, they are not pocket friendly for low-resource-income countries. Hence, with the advent of green factory biotechnology, plant-derived edible vaccines are such a promising approach to supplement conventional vaccine methods. Human travellers are often the major transmitters as they move from region to region. Poor sanitation and inadequate clean water supply are services not readily available in most Sub-Saharan African countries, coupled with insufficient surveillance services, lack of early detection facilities, and the public not having ample awareness concerning sanitation and hygiene. This article highlights the epidemiology of cholera in Africa and expounds on what drives the outbreaks of cholera in this region. The discussion provides an in-depth analysis of the factors leading to the forsaken cholera drivers, emphasizing economic factors, culture, and environmental influences, particularly within the Sub-Saharan African communities. It presents a strategic blueprint approach that includes public health awareness, community participation, government involvement, and exploring emerging research tools. By merging these proposals into a unified context, a collective and practical methodology would be established to tackle the impact of cholera epidemiology that has been sidelined in Sub-Saharan Africa.
Keywords: African Research